2022
DOI: 10.1021/acs.jmedchem.2c01496
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of Halofuginone Derivatives as ATP-Aided Inhibitors Against Bacterial Prolyl-tRNA Synthetase

Abstract: Aminoacyl-tRNA synthetases (aaRSs) are promising antimicrobial targets due to their essential roles in protein translation, and expanding their inhibitory mechanisms will provide new opportunities for drug discovery. We report here that halofuginone (HF), an herb-derived medicine, moderately inhibits prolyl-tRNA synthetases (ProRSs) from various pathogenic bacteria. A cocrystal structure of Staphylococcus aureus ProRS (SaProRS) with HF and an ATP analog was determined, which guided the design of new HF analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…[24] ). 1 3-Aminopyrazine-2-carboxamide (III): Into a 10 mL MW tube containing 1.0 mmol of 3-chloropyrazine-2-carboxamide (II), 5 mL (excess) of 7 N ammonia in anhyd. methanol (Merck) was added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] ). 1 3-Aminopyrazine-2-carboxamide (III): Into a 10 mL MW tube containing 1.0 mmol of 3-chloropyrazine-2-carboxamide (II), 5 mL (excess) of 7 N ammonia in anhyd. methanol (Merck) was added.…”
Section: Discussionmentioning
confidence: 99%
“…Natural alkaloid febrifugine (Figure 1a) and its derivatives, including halofuginone (HFG, Figure 1b), are ProRS inhibitors that occupy both L-Pro and tRNA binding sites of the enzyme. [1] They exhibit excellent properties against malaria, fibroproliferative diseases, or cancer. [2][3][4][5] However, both the antimalarial and antifibrotic activity of HFG are negatively affected by the accumulation of Pro due to the prolinecompetitive nature of the binding.…”
Section: Introductionmentioning
confidence: 99%
“…Halofuginone, a synthetic derivative of the natural product febrifugine, exhibits potent inhibitory activities against both protozoan parasites and numerous cancer cells ( Derbyshire et al, 2012 ; Zhang et al, 2012 ; McLaughlin et al, 2014 ; Herman et al, 2015 ; Bellini et al, 2020 ; Cheng et al, 2022 ). In Eimeria , it was shown that halofuginone inhibits the invasion of sporozoites into host cells at an early stage of the life cycle and later disrupts the development of schizonts ( Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%